The use of quantitative fetal fibronectin for the prediction of preterm birth in women with exposed fetal membranes undergoing emergency cervical cerclage. (March 2020) - Suff, Natalie; Hall, Megan; Shennan, Andrew; Chandiramani, Manju
Abstract: Objective: Emergency cervical cerclage is often considered a controversial salvage measure for those pregnancies at high risk of mid-trimester loss or early preterm birth. To determine the efficacy and benefit of emergency cerclage insertion, we assessed the predictive value of quantitative fetal fibronectin (fFN) concentration in cervicovaginal fluid for spontaneous preterm birth in women with exposed fetal membranes prior to cerclage insertion. Study design: This was a retrospective observational study from St Thomas' Hospital, London of a cohort of women with singleton pregnancy and exposed fetal membranes presenting between 18 and 23 +6 weeks of gestation (n = 35), in the period 2015-2018. fFN concentrations in cervicovaginal fluid were measured quantitatively at presentation in all women within 24 h prior to cerclage insertion. Results: 35 eligible women with exposed fetal membranes who underwent an emergency cervical cerclage were identified. The median gestational age was 20 + 0 weeks (18 + 6−21 + 2) at presentation and 29 + 3 weeks (23 + 3−38 + 2) at delivery, with a median time from emergency cerclage to delivery of 65.5 days (17–126.5). In total, 12 women (34 %) delivered within 28 days of emergency cerclage insertion. 60 % of women with an fFN level above 500 ng/mL delivered within 28 days of cerclage insertion, and they all delivered before 37 weeks gestation. No women with fFN levels below 10 ng/mL delivered within 28 days and 75 % of these women delivered at term. Concentration of quantitative fFN at presentation correlated negatively with time to delivery (Spearman's rs = −0.52, p = 0.0016). Mann–Whitney U analysis demonstrated a significant difference in the distribution of qfFN concentrations in women who delivered preterm compared to those who did not, both within 28 days from testing (p = 0.0048) and <37 weeks (p = 0.006). Conclusion: Quantitative fFN has a role in predicting spontaneous preterm birth even in women with exposed fetal membranes undergoing emergency cervical cerclage. Given the serious risks associated with cervical cerclage surgery, qfFN could be used to counsel these patients at high risk of preterm delivery, as well as assisting in the decision to insert a cerclage.